The Role of Wife as a Family Economic Supporter of the Shari'ah Maqosid Perspective on Working Workers - Imron, M.; Algifari, Muhammad Faiz (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Wives working in this day and age are not new, there are a lot of wives who work to help support the family economy. This study aims to find out the wife helping to work to support the family income at CV Sindang Kasih Legi in Pageraji Village, Cilongok District, Banyumas Regency reviewed in the context of sharia maqosid. The type of research is field research with a qualitative approach. Primary data is sourced from interviews with five wives who work at CV Sidang Kasih Legi while secondary data comes from books, journals and other documents. The author's data collection technique uses observation, interview, and documentation methods. Furthermore, the data was analyzed using descriptive techniques. Based on the results of the research, it was concluded that the wife worked to support the family income from the perspective of the sharia maqosid at CV Sindang Kasih Legi in accordance with the sharia maqosid, namely being able to maintain religion, intellect, soul, descendants and property and there were those who were included in the darūriyyah level, namely Mrs. Masiroh who worked at the CV because her husband was sick, so Mrs. Masiroh became the backbone of the family for the sake of the survival of her family, some also entered at the level of ḥājiyyah such as Mrs. Casem, Mrs. Narti, Mrs. Hidayah, and Mrs. Maliyatun because their husbands are still working and their income, the wives who work only provide convenience in fulfilling the needs of a better and decent life, for the level of taḥsiniyat which is only a refinement and complement for the The wife who works at CV Siding Kasih Legi who was interviewed by the researcher does not fall into this category. So that the wife who supports the family economy from the perspective of the sharia maqoosid in CV Sindang Kasih Legi in accordance with the sharia maqosid is at the darūriyyah level such as Mrs. Maisaroh, and there are at the ḥājiyyah level such as Mrs. Casem, Mrs. Narti, Mrs. Hidayah, and Mrs. Maliyatun.